Dramatic Improvement of Severe Cryptococcosis‐Induced Immune Reconstitution Syndrome With Adalimumab in a Renal Transplant Recipient. Issue 2 (21st January 2015) - Scemla, A.; Gerber, S.; Duquesne, A.; Parize, P.; Martinez, F.; Anglicheau, D.; Snanoudj, R.; Zuber, M.; Bougnoux, M.‐E.; Legendre, C.; Lortholary, O.
<x xml:space="preserve">Abstract</x> In solid organ transplant recipients, immune reconstitution inflammatory syndrome (IRIS) is a rare complication of cryptococcosis, which may require steroids in its most severe forms. Here, we report the case of a renal transplant recipient who developed severe cryptococcal meningitis‐associated IRIS 1 week after immunosuppression reduction. High‐dose steroids failed to improve the disease. Finally, a recombinant human monoclonal tumor necrosis factor‐α (TNF‐α) antagonist, adalimumab, was prescribed, and the patient rapidly experienced dramatic neurological improvement. No IRIS relapse occurred within 14 months following adalimumab discontinuation.